Devastating neurologic injuries in the Syrian war. Issue 1 (February 2019) - El Hajj Abdallah, Yasmeen; Beveridge, Julie; Chan, Ming; Deeb, Taha; Mowafi, Hani; Al-Nuaimi, Saleem; Easa, Abdulkader Saed; Saqqur, Maher
Abstract : Background: Since 2011, hundreds of thousands of Syrians have been displaced and injured due to the ongoing Syrian civil war. In this study, we report the prevalence of neurologic injuries in a major rehabilitation center on the Turkish–Syrian border where death and injury tolls continue to rise. Method: Based on several on-site visits from 2013 to 2016, medical practitioners collected data from patients in the major rehabilitation center on the border of Turkey and Syria. The clinical data, which included the type and cause of injury, laterality, paralysis, areas injured, and treatment offered, were analyzed. Results: A total of 230 patients were identified as having sustained a neurologic injury, 221/230 (96.1%) male and 9/230 (3.91%) female, ranging from ages 2–52 years. A total of 305 total injuries were documented over the course of a 4-year analysis due to several patients having multiple injuries. Gunshot wounds were the dominant mechanism of injury in 125/230 (54.3%) patients. Patients more frequently sustained single injuries 152/230 (66.1%) than multiple injuries 78/230 (33.9%). Peripheral nerve injuries were the most prevalent injuries, at 92.5% of all neurologic injuries (282/305), specifically injury to the radial nerve, at 19.1% (54/282) of peripheral injuries. Patients with spinal cord injuries made up 20/230 (8.7%) of all patients, with thoracic spine injuries composing 50% (10/20). Traumatic brain injuries were the least prevalent, 3/230 (1.3%), with an equal distribution of subtypes. Conclusion: This study and critical analysis of the devastation in Syria suggests the desperate need for emergency aid.